Physiological adaptation to irradiance in duckweeds is species and accession specific and depends on light habitat niche - Smith, Kellie E (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology.